Secular trends in incidence and recurrence rates of hip fracture: a nationwide population-based study. Issue 3 (March 2017) - Chen, F.-P.; Shyu, Y.-C.; Fu, T.-S.; Sun, C.-C.; Chao, A.-S.; Tsai, T.-L.; Huang, T.-S.
Abstract Summary We assessed the incidence of hip fracture and second hip fractures in Taiwan from 2001 to 2012. Age-standardized incidence rates decreased after 2005. However, mortality rate after first hip fracture was substantial compared to second hip fracture rate in a competing risk model. Introduction The aim of the study is to assess the incidence rates (IRs) of hip fractures, including changes in trends and medical costs, and second hip fractures in the Taiwanese population. Methods The number of hip fractures and the associated medical costs were obtained from the annual report of the Ministry of Health and Welfare, Taiwan, for individuals ≥50 years of age. The data of population at risk were retrieved from annual population reports from the Ministry of the Interior, Taiwan. The incidence of second hip fractures was evaluated from the National Health Insurance Research Database of Taiwan for insured individuals aged ≥50 years from 2001 to 2011 with follow-up until 2013 using a competing risk model. Results The IR for the entire population increased from 332.7 to 336.5 per 100, 000 person-years during 2001–2005 and decreased thereafter. This secular change was driven by a decrease in hip fractures for both men and women. The 10-year cumulative incidence rate of second hip fracture was 11.2% (95% CI 11.0–11.5%) in women and 7.9% (95% CI 7.6–8.1%) in men. Adjusted by consumer price index (CPI), the costs of hospitalization due to hip fracture increased from NTD 1.17 billion in 2001 to NTD 1.43 billion in 2012. However, the CPI-adjusted costs of each admission decreased from NTD 74944 in 2001 to NTD 65791 in 2012. Conclusions Since 2006, the IR of hip fractures has been declining in Taiwan. The 10-year cumulative IR of mortality is substantial for individuals who with first hip fracture.